Gauging the Welfare Effects of Shocks in Rural Tanzania - Christiaensen, Luc; Hoffmann, Vivian; Sarris, Alexander (World Bank, Washington, DC, 2012)
Studies of risk and its consequences tend to focus on one risk factor, such as a drought or an economic crisis. Yet 2003 household surveys in rural Kilimanjaro and Ruvuma, two cash-crop-growing regions in Tanzania that experienced a precipitous coffee price decline around the turn of the millennium, identified health and drought shocks as well as commodity price declines as major risk factors, suggesting the need for a comprehensive approach to analyzing household vulnerability. In fact, most coffee growers, except the smaller ones in Kilimanjaro, weathered the coffee price declines rather well, at least to the point of not being worse off than non-coffee growers. Conversely, improving health conditions and reducing the effect of droughts emerge as critical to reduce vulnerability. One-third of the rural households in Kilimanjaro experienced a drought or health shocks, resulting in an estimated 8 percent welfare loss on average, after using savings and aid. Rainfall is more reliable in Ruvuma, and drought there did not affect welfare. Surprisingly, neither did health shocks, plausibly because of lower medical expenditures given limited health care provisions.